2021
DOI: 10.3390/ijms222413421
|View full text |Cite
|
Sign up to set email alerts
|

Distal Lung Microenvironment Triggers Release of Mediators Recognized as Potential Systemic Biomarkers for Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with an unmet need of biomarkers that can aid in the diagnostic and prognostic assessment of the disease and response to treatment. In this two-part explorative proteomic study, we demonstrate how proteins associated with tissue remodeling, inflammation and chemotaxis such as MMP7, CXCL13 and CCL19 are released in response to aberrant extracellular matrix (ECM) in IPF lung. We used a novel ex vivo model where decellularized lung tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 94 publications
0
7
0
3
Order By: Relevance
“…Studies have confirmed that many proteins related to the acquired immune system, such as anti-heat shock protein- (HSP-) 70 antibodies [ 57 ], C-X-C motif chemokine 13 (CXCL13) [ 58 ], anti-vimentin antibodies [ 59 ], and some T-cell subpopulations, might be associated with worse prognosis, acute exacerbations, and pulmonary hypertension. Thus, these proteins could be used as objective biomarkers in the diagnosis of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that many proteins related to the acquired immune system, such as anti-heat shock protein- (HSP-) 70 antibodies [ 57 ], C-X-C motif chemokine 13 (CXCL13) [ 58 ], anti-vimentin antibodies [ 59 ], and some T-cell subpopulations, might be associated with worse prognosis, acute exacerbations, and pulmonary hypertension. Thus, these proteins could be used as objective biomarkers in the diagnosis of IPF.…”
Section: Discussionmentioning
confidence: 99%
“…In lung epithelial cells, MMP7 regulates β-catenin to promote wound healing and tissue remodelling [16] and is therefore necessary for homeostatic maintenance of tissue [17]. However, pathological epithelial cell dysfunction may occur later in the fibrogenic process, perhaps because of a dysregulated and fibrotic ECM, which is known to drive IPF pathology [18][19][20][21]. It is also possible that there is fibroblast-like cell which expresses MMP7 that drives honeycomb cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in good agreement with the recent PROFILE (Prospective Observation of Fibrosis in the Lung Clinical Endpoints) study conclusions indicating that serum SP-D and MMP-7 could best differentiate between IPF patients and controls [139,140]. In addition, recent studies using a proximity extension assay identified higher protein levels of MMP-7, IL-6, NOS3 and CASP-8 in PF progressive patients compared to stable patients at follow-up, due to the importance of vascular and remodeling processes linked to progression of the disease [141]. However, recent studies question if MMP-7 is related to PF prognosis [35,142].…”
Section: Mmp-7mentioning
confidence: 99%